2013
DOI: 10.1016/j.heares.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation for chronic electrical stimulation in the mouse

Abstract: The mouse is becoming an increasingly attractive model for auditory research due to the number of genetic deafness models available. These genetic models offer the researcher an array of congenital causes of hearing impairment, and are therefore of high clinical relevance. To date, the use of mice in cochlear implant research has not been possible due to the lack of an intracochlear electrode array and stimulator small enough for murine use, coupled with the difficulty of the surgery in this species. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…SGNs were identified within Rosenthal’s canal and counted. Only SGNs exhibiting a clear nucleus were counted using previously published techniques [32, 33, 51, 55, 56]. Data was collected from five non-continuous sections with a separation of 72 μm ensuring that no cell was counted more than once.…”
Section: Methodsmentioning
confidence: 99%
“…SGNs were identified within Rosenthal’s canal and counted. Only SGNs exhibiting a clear nucleus were counted using previously published techniques [32, 33, 51, 55, 56]. Data was collected from five non-continuous sections with a separation of 72 μm ensuring that no cell was counted more than once.…”
Section: Methodsmentioning
confidence: 99%
“…Connect the head-stage and pre-amplifier to the auditory processor via the optic fiber port. 5. Check the impedance of the active and reference electrode.…”
Section: Pre-deafening Acoustic Auditory Brainstem Response (Aabr)mentioning
confidence: 99%
“…Previous studies have shown the feasibility of CI implantation in mice 5,6,7 . Irving et al demonstrated that chronic intracochlear electrical stimulation can be achieved for up to one month.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the models by Frijns et al (1995); Malherbe et al 2013and Wong et al (2016)). Cat is also a popular experimental animal model (Hatsushika et al 1990) for which a 3D model has recently been developed (Kang et al 2015), while other experimental animal cochlear models like mouse (Irving et al 2013),…”
Section: Animal Modelsmentioning
confidence: 99%